FACTORS WHICH EXPECT CRIMES IN THE FIELD OF JUSTICE: SOCIAL AND PSYCHOLOGICAL DETERMINANTS - Ахмедов, Вусал Алігісмат огли (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Objective: to reveal a complex of determinants of crimes against justice, that is, objectively existing phenomena and processes that determine the commission of these crimes. Methods of research: the methodological basis of the study consisted of general scientific methods of cognition, through which identified personal and socio-economic factors of crimes against justice. Results: the author identifies complex determinants of crimes against justice in their totality of interconnections. Discussion: the author suggests investigating the relationship between the social and psychological determinants of crimes against justice. Discuss the thesis that the crime is the result of the interaction of internal moral attitudes and values of the individual with the circumstances of the environment and social conditions. Under the factors of crime against justice, it is fully justified to understand such negative socio-economic, socio-psychological and legal phenomena and processes that have different determinants, including those of a casual nature, but in their totality and interaction generate, promote, modify and condition the existence and manifestations of such crime. Among the criminogenic factors of crime, apart from ideological, socio-psychological, legal and organizational and managerial, according to some researchers, the factors are of socio-economic nature. Crimes against justice as a whole, as a social phenomenon, are the result of the interaction of objective factors of the environment and subjective factors of the individual. A distinctive feature of the determination complex of the crimes in question is the existence of a conflict between different parties to criminal proceedings. Persons committing such crimes are inevitably confronted with their opponents in a criminal proceeding. This circumstance directly affects the motivation of committing crimes against participants in criminal proceedings. In general, the conflict situation, which develops in connection with the administration of justice, in most cases, stimulates the commission of a crime, because before the person in this case, there are great opportunities for unlawful satisfaction of their needs and interests. Based on the analysis of materials of investigative and judicial practice and legal literature, the reasons and conditions that facilitate the commission of crimes against justice include: imperfection of the current legislation (especially it can be traced in the investigation of such crimes as non-enforcement of a court decision); shortcomings of recruitment in law enforcement agencies; shortcomings in the professional training of law enforcement officers; presence of ineffective system of responsibility of judges; violation of service discipline; the lack of effective educational work among law enforcement officers, including the staff of penitentiary institutions; inadequate control over the activities of pre-trial investigation bodies; corrupt law enforcement agencies; inadequate service by the employees of the penitentiary service in relation to the protection and security of prisoners, non-compliance with the regime requirements for conducting search activities and the removal of prohibited items; failure to take appropriate measures to secure the isolation of convicts, leading to escapes from places of detention; the dependence of the assessment of the activity of law enforcement agencies on the ratio of the number of detected crimes and the number of registered applications, reports of crimes; miscalculations in the operations of the operational units for the detection, prevention and disclosure of crimes committed in the colonies, as well as violations of the established procedure for serving sentences; low level of legal awareness of the population. At the same time, the main component of such crimes is primarily internal determinants associated with the personality of the offender. Thus, a significant number of convicts have intrinsic deep moral and psychological deformation, pathology of mental condition, defects of legal consciousness. The relationship between the social and psychological determinants of crimes against justice is evident. After all, in the same socio-economic conditions, different personalities behave in different ways, and not every person chooses a criminal way to meet their needs and interests. Therefore, the crime committed is the result of the interaction of internal moral attitudes and values of the individual with the circumstances of the environment and social conditions.